Given that and are the roots of the quadratic equation above.
If is positive and formed a geometric progression , compute .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 2 − ( 3 p − 2 ) x + ( 2 p + 8 ) = 0
Given that the roots are x 1 and x 2 . From Vieta's formula,
x 1 + x 2 = 3 p − 2 x 1 x 2 = 2 p + 8
Now, we know that x 1 , p , x 2 forms a GP, therefore,
r = x 1 p = p x 2 ⟹ p 2 = x 1 x 2
Substitute this into the product of roots:
p 2 = 2 p + 8 p 2 − 2 p − 8 = 0 ( p − 4 ) ( p + 2 ) = 0 p = 4 , − 2
It is given that p > 0 , therefore, p = 4 . From sum of roots,
x 1 + x 2 = 3 p − 2 x 1 + p + x 2 = 4 p − 2 = 4 ( 4 ) − 2 = 1 4